2018
DOI: 10.31211/interacoes.n35.2018.a2
|View full text |Cite
|
Sign up to set email alerts
|

Pension Policy Dimension to Ghanaian Workers’ Housing Needs Provision

Abstract: The paper explores workers’ housing needs, expectations and pension policy compatibility to meeting this need using the pension system as a mortgage facility. Use was made of a cross-sectional design. A sample of 131 workers was selected through convenient sampling. The findings show that workers have need for houses with retirement in focus and that they expect government to provide them with affordable houses. Government’s provision of these housing needs can purportedly be met via the national pension syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…A house is a vital safety need [4], the non-existence of which presents workers with one of the greatest challenges in post-retirement life. House acquisition is "the purchase or securing of a house for use as a residential facility with retirement in focus" [5]. In a study conducted by reference [6] on the topic 'systematic preparation process and resource mobilization towards post-retirement life in urban Ghana: An exploration', it was observed that the indirect financial actions undertaken in preparing for post-retirement life, medical actions (28.13%) and finding a place of residence to relocate to after retirement (50.63%) are the most commonly indicated options [6].…”
Section: Housing Issues In Ghanamentioning
confidence: 99%
See 3 more Smart Citations
“…A house is a vital safety need [4], the non-existence of which presents workers with one of the greatest challenges in post-retirement life. House acquisition is "the purchase or securing of a house for use as a residential facility with retirement in focus" [5]. In a study conducted by reference [6] on the topic 'systematic preparation process and resource mobilization towards post-retirement life in urban Ghana: An exploration', it was observed that the indirect financial actions undertaken in preparing for post-retirement life, medical actions (28.13%) and finding a place of residence to relocate to after retirement (50.63%) are the most commonly indicated options [6].…”
Section: Housing Issues In Ghanamentioning
confidence: 99%
“…The acquisition of a house enables the saving of money that would otherwise be required for renting an apartment in old age. Such money could be channeled into meeting select survival needs [5]. This is a factor in the relatively low levels of pension incomes in Ghana [21].…”
Section: Housing Issues In Ghanamentioning
confidence: 99%
See 2 more Smart Citations
“…It may occur at both the organizational and individual levels comprising savings and the accumulation of assets among others (Dovie, 2017). Retirement planning consist of family planning and the allocation of resources for designated purposes namely purchase of houses (Dovie et al, 2018;Dovie, 2019aDovie, , 2019bDovie, , 2019c or paying for the education of children while simultaneously instituting retirement plans and portfolios (Dovie, 2018a). Preparation towards retirement also entails family planning and social relationship building which takes three distinct forms namely having a manageable family size, care for own children, care for siblings and/or cousins as well as joining association(s).…”
Section: Introductionmentioning
confidence: 99%